Wykorzystanie pochodnych instrumentów zabezpieczających przez polskie przedsiębiorstwa notowane na GPW - Klimczak, Karol M. (The Use of Derivative Hedging Instruments in Polish Listed Companies, 2006)
The rationales for corporate risk management are examined on the basis of financial statement analysis. From among Polish non-financial companies listed on the Warsaw Stock Exchange, the ones employing risk management techniques are identified through keyword analysis. Subsequently, the financial characteristics of companies are examined using parametric tests and logic regression to verify hypothetical rationales for implementing risk management. However, the only relationship identified is with company size. For other rationales - costs of financial distress, tax shield, and securing investment financing - no proof is found in the sample analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 305-315